SOCIAL CLASS AND INEQUALITY - Bonstead-Bruns, Melissa (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Welcome to SOC 314 Social Class and Inequality! I have four objectives for this course. The first is to familiarize you with "the canon" of literature that anyone coming out of this course would be expected to know. This will entail learning the classic theories of social class and inequality as well as current approaches to the issue. Secondly, we will examine the current state of inequality along with current trends in inequality. Specifically, we will look at inequality in power and prestige as well as economic inequality. Thirdly, we will concentrate specifically on the intersection of gender, race, and class as sources of inequality. Finally, we will address various policy issues that are designed to address problems of inequality.